2006
DOI: 10.1001/archneur.63.11.1605
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations in the Guanosine Triphosphate Cyclohydrolase 1 Gene Associated With DYT5 Dystonia

Abstract: To better understand the relationship between mutation of the guanosine triphosphate cyclohydrolase I (GCH1) gene and the etiology of DYT5 dystonia and to accumulate data on the mutation in the Japanese population for genetic diagnosis of the disease. Setting: Japanese population. Patients: Eight Japanese patients with suspected DYT5 dystonia were analyzed. Intervention: Direct genomic sequencing of 6 exons of GCH1 was performed. Main Outcome Measures: For patients who did not exhibit any abnormality in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…Since 1994, more than 100 mutations of the GCH1 gene have been reported in DRD patients from different ethnic populations 6, 23. Although it is a very interesting topic, the reason why the GCH1 gene has so many different mutations in its coding region (including the splice sites) is yet to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1994, more than 100 mutations of the GCH1 gene have been reported in DRD patients from different ethnic populations 6, 23. Although it is a very interesting topic, the reason why the GCH1 gene has so many different mutations in its coding region (including the splice sites) is yet to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…p.K224R has been so far reported in three pedigrees associated with athetoid cerebral palsy (family Hu in Bandmann et al 1998), myoclonic dystonia (Leuzzi et al 2002) and adult-onset gait dystonia, rigidity and bradykinesia (Patient D97 in Garavaglia et al 2004). Since the first report (Furukawa et al 2000), few pedigrees harbouring gross deletion of the GCH1 gene have been reported (Klein et al 2002;Hagenah et al 2005;Ohta et al 2006;Clot et al 2009). Their phenotype overlaps with that of patients with less severe alterations.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports of GCH1 mutations detected in two families in the same geographical region in Germany [22], France [23] and Italy [24]. Two apparently unrelated patients with a new mutation have recently been described in Japan [16] suggesting a common origin of the mutated chromosomes. Both Tassin et al and Uncini et al detected a common haplotype for four microsatellite markers in the GCH1 region which segregated with the respective mutation found in the French and Italian families.…”
Section: Discussionmentioning
confidence: 99%
“…This number of carriers of the mutation was much higher than expected, given a worldwide estimated prevalence of 0.5 per million for DRD [13], although this may be underestimated owing to underdiagnosis. Furthermore, most mutations in GCH1 are private [16]. Consequently, the finding of the same mutation in family members from two pedigrees with DYT5 dystonia who were originally thought to be unrelated prompted us to consider the possibility that our cohort may have descended from a single founder.…”
Section: Introductionmentioning
confidence: 99%